NSUN4‐dependent m5C modification facilitates mitochondrial fission to accelerate diabetic nephropathy process via regulating SMURF1/CAMK1 axis - Danyi Yang; Yinyin Chen; Hao Li; Guoyong Liu; Yang Gao; Liyu He (Clinical and Translational Medicine, 2026)
Abstract Background NOP2/Sun RNA methyltransferase family member 4 (NSUN4)‐mediated 5‐methylcytosine (m5C) modification has been implicated in diabetes‐related diseases. However, its role and molecular mechanism in diabetic nephropathy (DN) remain unclear. Methods DN mouse model was constructed by injecting with streptozotocin (STZ). High glucose (HG)‐induced HK‐2 cells were used to establish a cellular model of DN. The levels of NSUN4, SMAD ubiquitination regulatory factor 1 (SMURF1), calcium/calmodulin‐dependent protein kinase 1 (CAMK1), and mitochondrial‐related proteins were analyzed using qRT‐PCR, western blot, or immunohistochemical staining. Renal injury in mice was evaluated using relevant kits and histological staining. Cell apoptosis, ROS production and proliferation were examined by TUNEL, dihydroethidium, MitoSOX Red and EdU staining. The interaction between SMURF1 and Aly/REF export factor (ALYREF) or CAMK1 was confirmed by RNA immunoprecipitation, Co‐IP and ubiquitination assay. Results Upregulation of NSUN4 increased the m5C level in DN. Knockout of NSUN4 alleviated STZ‐induced renal injury in mice by repressing renal tubule cell mitochondrial fission and promoting mitochondrial fusion. NSUN4 downregulation reduced mitochondrial fission and promoted mitochondrial fusion to relieve HG‐induced HK‐2 cell apoptosis. NSUN4‐mediated m5C modification promoted SMURF1 mRNA stability by regulating ALYREF. SMURF1 overexpression rescued the suppressive effect of NSUN4 knockdown on cell mitochondrial fission and apoptosis. Besides, SMURF1 facilitated the ubiquitination and degradation of CAMK1. Furthermore, sh‐CAMK1 abolished the inhibitory effect of sh‐SMURF1 on cell mitochondrial fission and apoptosis. Meanwhile, downregulation of NSUN4 relieved STZ‐induced renal injury in DN mice by reducing mitochondrial fission via the SMURF1/CAMK1 axis. Conclusion NSUN4‐mediated upregulation of SMURF1 promoted mitochondrial fission to accelerate DN progression via increasing CAMK1 ubiquitination. The discovery of the NSUN4/SMURF1/CAMK1 axis provides new insights into DN pathogenesis.